A Triboelectric Generator Based on Checker‐Like Interdigital Electrodes with a Sandwiched PET Thin Film for Harvesting Sliding Energy in All Directions. Issue 1 (4th August 2014) - Guo, Hengyu; Leng, Qiang; He, Xianming; Wang, Mingjun; Chen, Jie; Hu, Chenguo; Xi, Yi
<x xml:space="preserve">Abstract</x> A triboelectric generator based on checker‐like interdigital electrodes (TEGC) with a sandwiched polyethylene terephthalate (PET) thin film that can convert translation kinetic energy in all directions to electricity is reported. The design of the sandwiched PET thin film can effectively avoid direct wear between metal electrodes and sliding panel. The mechanism of the TEGC is described in detail. The performance of the TEGC in different sliding directions is studied, indicating a maximum output power density of 1.9 W m‐2 and open‐circuit voltage of 210 V achieved in the X or Y sliding direction. The TEGC is used to charge a 110 μF commercial capacitor to 5 V in 35 s and light up two light‐emitting diodes (LEDs) connected with the capacitor simultaneously. The TEGC based mouse pad and sliding panel are fabricated to harvest mouse operation energy to light up LEDs connected in antiparallel when the computer mouse operates a game. The TEGC has advantages of being flexible, light weight, durable, cost effective, and portable by folding or rolling into a small part. This work presents a significant progress toward the structure design of triboelectric generator for its practical applications.